Tarybų Lietuvos bibliotekų kadrai 1940–1941 metais - Sinkevičius, Klemensas (Knygotyra, 1983)
After the Soviet rule was restored in Lithuania in the sommer of the year 1940, there began a rapid development of libraries. During the year of Soviet rule the number of the regular library staff has grown 3–4 times. The state and the Party authorities have done a lot work selecting and training new librarians. At the same time there began the preparation of library cadres in the Kaunas Folks-University courses of librarianship and the Chair of bibliology was established in the Vilnius State University. All these works and plans were completely discontinued by the Naci-German agression.